Cerita Bergambar sebagai Strategi Menumbuhkan Kepedulian Sosial dan Daya Paham terhadap Bacaan - Siti Rukayah; Daroe Iswatiningsih (Badan Penerbit STIEPARI Press, 2025)
This study aims to examine the effectiveness of picture stories as a learning strategy to improve reading comprehension and foster social awareness among third-grade elementary students. The research is motivated by ongoing challenges in cultivating students’ interest in reading and instilling essential social values from an early age. This qualitative study employed a case study design conducted in a third-grade classroom. Data were collected through observation, interviews, and documentation. The findings show that the use of picture stories significantly increased students' engagement with reading. The combination of text and illustration helped students understand the story content, grasp meanings, and develop emotional connections with characters and events. Furthermore, picture stories encouraged peer discussions, allowing students to express opinions, reflect on moral values, and relate them to real-life experiences. These interactions contributed to the development of empathy, cooperation, and social care. Teachers also found it easier to deliver lessons contextually and enjoyably through this medium. It can be concluded that picture stories are effective not only in enhancing reading comprehension but also in nurturing social awareness among elementary students.